Beer and Racism 2020
DOI: 10.1332/policypress/9781529201758.003.0007
|View full text |Cite
|
Sign up to set email alerts
|

#WeAreCraftBeer: Contemporary Movements to Change the Whiteness of Craft Beer

Abstract: This chapter explains that although the central story of race and beer in the United States is one that centers on the production and reproduction of whiteness, there is reason to believe that the racialized social structure of beer might be cracking. It looks at several developments that may indicate critical change in the phenomenon of craft beer. There is no doubt that there are several contemporary currents that are pressing against the whiteness of craft beer, and there is also no doubt that it is all hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…One emergent pattern in the data for this larger research project (but not fully explored here) is that a number of workers who are women and people of color may be accessing alternative career pathways within the craft beer industry less dictated by pure passion and the privileged statuses that frame it. Expressing different relationships to their jobs-for instance, by voicing social justice advocacy through their employment platform-could be a source of strategic advantage for some workers in an era when more organizations are publicly signaling their support for diversity, equity, and inclusion initiatives (see Chapman and Brunsma 2020;Wilson and Stone 2022). As an alternative cultural logic of work that highlights social identity issues, especially those that are underrepresented, the popularization of this narrative could potentially support the upward mobility of workers from marginalized social groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One emergent pattern in the data for this larger research project (but not fully explored here) is that a number of workers who are women and people of color may be accessing alternative career pathways within the craft beer industry less dictated by pure passion and the privileged statuses that frame it. Expressing different relationships to their jobs-for instance, by voicing social justice advocacy through their employment platform-could be a source of strategic advantage for some workers in an era when more organizations are publicly signaling their support for diversity, equity, and inclusion initiatives (see Chapman and Brunsma 2020;Wilson and Stone 2022). As an alternative cultural logic of work that highlights social identity issues, especially those that are underrepresented, the popularization of this narrative could potentially support the upward mobility of workers from marginalized social groups.…”
Section: Discussionmentioning
confidence: 99%
“…Many brewery owners, for instance, describe their companies as "passion projects," which also doubles as a prominent form of branding within the industry (Koontz and Chapman 2019). Demographically, however, craft beer workers remain overwhelmingly white, male, and relatively middle class (Chapman and Brunsma 2020;Withers 2017). This raises questions about the role passion for work may play in perpetuating social inequalities within these types of settings and potentially contributing to the marginalization of women and people of color within the industry.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth noting that this is one of the more ethnically and racially diverse parts of the state, largely reflecting the diversity of nearby New York City (United States Census Bureau, 2020b). The fact that craft breweries struggle to engage diverse consumers (Matthews and Patton, 2016) and are largely perceived as catering to white people (Chapman and Brunsma, 2020) is problematic for growth in this area of northern New Jersey. Nonetheless, the growing movement of neolocalism Source: Created by the authors using data from the organization New Jersey Craft Beer (2023) and confirmed via evaluation of breweries progress toward an opening date (i.e., evaluation of physical space, website, and social media presence/communication).…”
Section: Future Of Craft Beer In New Jerseymentioning
confidence: 99%